Kontribusi Praktek Kerja Industri dan Motivasi Belajar Terhadap Sikap Wirausaha - Aranmus, Aranmus (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
This study aims to determine how much the contributions industry practices and student motivation on attitudes to entrepreneurship. The study was conducted on students of SMK Negeri 1 Tembilahan Hulu with a sample of 38 students and collecting data using questionnaires and documentation. The result showed that the industry practices and student motivation has a higher contribution to the students' entrepreneurial attitude. The conclusion of this research is to improve the quality of graduates of vocational schools should place students in appropriate and relevant industries. In addition, provide an understanding of student motivation in order to encourage students to have an entrepreneurial attitude and be able confront the challenges in the world of work and life.